Comparative analysis on temperature characteristics of hydrogen-powered and traditional fossil-fueled vehicle fires in the tunnel under longitudinal ventilations. (5th July 2022) - Xie, Yongliang; Lv, Na; Huang, Yan; Wu, Dejian; Gong, Liang; Yang, Xufeng; Zeng, Yikai
Abstract: Vehicle fires in the tunnel are a great threat to the safe operation of the tunnel. Due to the rapid development of the hydrogen economy, the fire due to the hydrogen leakage could not be avoided and may bring great damage to the passengers and infrastructure. Due to the large difference between pool fires of traditional fossil-fueled and jet fires of hydrogen-powered vehicles, it is in doubt whether the existing longitudinal ventilation design could still be effective for the safety issue of hydrogen powered vehicles. To solve this problem, it is necessary to compare temperature characteristics of hydrogen-powered and traditional vehicle fires with and without longitudinal ventilations. In present work, we conducted a numerical investigation to discuss the different temperature distributions of traditional and hydrogen-fueled vehicle fires. Results indicate that the high temperature zone of the pool fire only exists above the ceiling of the vehicle. For hydrogen-powered vehicle fire, the high-speed hydrogen jet with the strong inertial force could push the hot smoke flows back to the ground. The ceiling temperature of hydrogen-powered vehicle fire is larger since hydrogen-powered vehicle has a larger heat release rate and the fire hazard of jet fires bring more danger compared with the pool fire. Although the temperature stratification is also obvious for the hydrogen-powered vehicle fire, the air temperature in the lower region could be heated and still high enough to bring a great damage to the passengers' lives. This is quite different with the traditional pool fire. In addition, the critical ventilation velocity is also discussed. The theoretical equation could well predicted the critical ventilation velocity of traditional vehicle fires. For hydrogen-powered vehicle fires, the critical ventilation velocity could reach up to 6 m/s. The theoretical equation could not well predict the critical ventilation velocity of hydrogen-powered vehicle fires due to exist of hydrogen jet fires. Highlights: Temperature characteristics of hydrogen and fossil-fueled vehicle fires are compared. Ceiling temperature of hydrogen vehicle fires are far larger than that of fossil vehicle fires. Theoretical equation could not well predict V cr of hydrogen vehicle fires.